Proceedings Title: Proceedings of the 2012 Winter Simulation Conference (WSC) 2012
DOI: 10.1109/wsc.2012.6465129
|View full text |Cite
|
Sign up to set email alerts
|

Autocorrelation effects in manufacturing systems performance: A simulation analysis

Abstract: Autocorrelation has been pointed out as one of the most challenging issues in manufacturing systems modeling. Numerical experimentation has shown that it may either enhance or harm performance. Furthermore, there is not yet a general agreement in what a realistic autocorrelation model is or whether it is actually relevant for practical applications. This paper provides a simulation analysis of the effects on performance caused by manufacturing process parameters following autoregressive (AR) processes. AR time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…These conclusions are also shared by Takahashi and Nakamura [51], Altiok and Melamed [52] and Pereira et al [53], who found that both positive and negative Corr(A) and Corr(S) have a negative impact on the performance of serial production lines.…”
Section: Auto-correlated Processessupporting
confidence: 61%
“…These conclusions are also shared by Takahashi and Nakamura [51], Altiok and Melamed [52] and Pereira et al [53], who found that both positive and negative Corr(A) and Corr(S) have a negative impact on the performance of serial production lines.…”
Section: Auto-correlated Processessupporting
confidence: 61%
“…They show that positively correlated arrivals spent more expected time in the system. Pereira et al (2012) evaluate the impact of correlation on assembly processes, serial lines and disassembly processes. They demonstrate that considering autocorrelation in modeling the process enhances the accuracy of estimated performance measures of the real system.…”
Section: Impact Of Correlation On the Performance Of Queuing And Manumentioning
confidence: 99%